Protein arginine methylation in transcription and epigenetic regulation - Pham, Hoang Quoc Hai; Tao, Xiaoqun; Yang, Yanzhong (Frontiers in Epigenetics and Epigenomics, 2023)
Arginine methylation is a prevalent post-translational modification (PTM) found in all eukaryotic systems. It involves the addition of a methyl group to the guanidino nitrogen atoms of arginine residues within proteins, and this process is catalyzed by a family of enzymes called protein arginine methyltransferases (PRMTs). In mammals, there exist nine PRMTs (PRMT1-9) that catalyze three distinct types of arginine methylation: monomethylarginine (MMA), asymmetric dimethylarginine (ADMA) and symmetric dimethylarginine (SDMA). These modifications play critical roles in numerous fundamental cellular processes, including transcription, RNA metabolism, genome maintenance, and signaling transduction. Aberrations in protein arginine methylation have been implicated in various human diseases, such as neurodevelopmental disorders and cancer. This review offers a general overview of arginine methylation, covering its deposition, its impact on protein function, and the diverse regulatory mechanisms involved. We specifically focus on an in-depth view of the role of arginine methylation in transcription and the epigenetic regulation of gene expression. Readers are directed towards additional reviews that encompass other aspects of arginine methylation biology.